The specialized educational service and multifunctional resource rooms: A look at the municipality of Sorocaba - Tomé, Lucimeire Prestes de Oliveira; Sandano, Wilson (Revista Hipótese, 2022)
This article demand, from a bibliographic, documentary and field research, to analyze the implementation and functioning of the Specialized Educational Service and Multifunctional Resource Rooms, in the period from 2010 to 2021, in the municipal schools of Sorocaba, regarding the services provided to students with disabilities, disorders and giftedness. It concludes that the services have met the population, but that there is a need for assertive actions by the local government.
Keywords: Multifunctional Resource Rooms; Municipal Schools of Sorocaba; Special Education